A Note on the Origins of Index Numbers - Chance, W. A. (The Review of Economics and Statistics, 1966)
Tacitus believed that the chief office of history is to prevent virtuous actions from being forgotten. That these few pages perform this office depends on the self-evident proposition that actions in support of economic knowledge are, in their nature, virtuous. In the history of economic thought the lineage of specific current doctrine or method at times takes on the tenuousness of a finely frayed thread that frustrates all efforts to distinguish the fibers comprising it. It often happens, in that circumstance, that the thread is knotted at some point short of its ultimate wanderings by a tacit agreement to recognize one or a few persons as the originators of the method or doctrine in question. When that happens, earlier efforts fall beyond the bounds of present memory. On occasion, however, it becomes possible to retie the knot somewhat farther back in the past. That is the function of the present note. currently accepted view 1 holds that the first recorded index number appeared in the work of G. R. Carli, an Italian who used a modified form of the simple average of relatives index number in 1764.2 This view probably originated with Wesley Mitchell, who named Carli as the inventor of the index number.3 In point of fact, this honor might be placed nearly a century earlier than Carli's effort, and certainly 25 years before it, depending on how strictly one chooses to define the term index number. If we give the term the broad meaning of a method or device which allows one to measure changes in aggregate price levels, we must consider a small book published by Rice Vaughan in the year 1675.4 Vaughan, an Englishman, was concerned with the rise in prices which had occurred in his native land over the preceding century. He wished to separate the influence on this price rise of the debasement of currency trom the intiuence of the heavy influx of gold and silver into Spain from the East and West Indies. In order to undertake this task, he required a measure of the general price rise which had occurred in that country. Vaughan relied on historic records of the wages of labor for his standard of measurement of price changes. Two considerations prompted his use of wages as a surrogate variable. First, labor carries with it a constant resultance of the Prices of all other things which are necessary for a Man's life. . Second, records of wages were more accessible than price data since statutes were readily available which always direct [ed] the rate of Labourers and Servants to be made with a regard of Prices of Victuals, Apparel, and other things necessary to their use. 6 Vaughan accordingly compared statutes setting wage rates for such labor as threshing grain and carpentry in the reign of Edward III with similar statutes of the period in which he wrote. On the assumption that these statutes reflected the costs to the laborer of his provisions, they served as ready-made index numbers. conclusion supported by these comparisons was that prices had risen to six or eight times their level of a century earlier.7 Those readers who insist that an index number must make explicit use of the prices to be measured are asked to consider the work of another Englishman of a slightly later period. In 1707, William Fleetwood, Bishop of Ely, published a defense of the fellows of a certain whose annual income from inheritances or pensions ran to more than five pounds.8 When the college was founded in the fifteenth century, its founders stipulated that a fellowship could be granted only to those students whose annual income from such sources was not in excess of that amount. A student of Fleetwood's acquaintance whose fellowship was in jeopardy appealed to the bishop. It was the student's contention that, in view of the past record of rising costs, an interpretation in the spirit of the regulation, rather than the letter, was more appropriate. student was perspicacious in his choice of * author is Assistant Professor of Economics at the University of Missouri. 1See, for example, John E. Freund and Frank J. Williams, Elementary Business Statistics: Modern Approach (Englewood Cliffs, New Jersey: Prentice-Hall, 1964), 77. 2Del Valore e della Proporzione de' Metalli Monetati con i generi in Italia prima delle Scoperte dell' Indie col confronto del Valore e della Proporzione de' Tempi nostri, in Custodi, Scrittori Italiani de Economia Politica, Parte Moderna, XIII, 297-366. 'Wesley C. Mitchell, The Making and Using of Index Numbers, Bulletin of the United States Bureau of Labor Statistics, 284 (Oct. 1921), 7. 'Rice Vaughan, A Discourse of Coin and Coinage (London: Th. Dawks, 1675). 5 Ibid., 107. 6 Ibid., 108. 7Ibid., 117-124. 8 William Fleetwood, Chronicon Preciosum: or, an Account of English Money, the Price of Corn, and Other Commodities, for the last 600 Years (London: Charles Harper, 1707).